What we already know about the effects of exercise in patients with fibromyalgia: An umbrella review - Sieczkowska S.M.* (2020)
© 2020 Elsevier Inc.We aimed to analyze the evidence on the effects of physical exercise in patients with fibromyalgia (FM) and to assess the characteristics of published studies, especially the quality of the evidence, through an umbrella review. This umbrella review followed the PRISMA guidelines and was documented in the PROSPERO registry (CRD42017075687). We searched the PubMed, Web of Science, SportDiscus, Scopus, Cinahl, and Cochrane Library databases. The methodological quality of systematic reviews was assessed using AMSTAR 2. We only selected systematic reviews (with or without meta-analyses) investigating the effects of any type of physical exercise in patients with FM syndrome. Thirty-seven systematic reviews (total = 477) fulfilled the criteria. Most studies were rated as being of low or moderate quality. A variety of exercises were used as treatment for FM symptoms, with positive results. Most of the reviews investigated the effects of aerobic exercise and strength training. No serious adverse events were reported. The largest effects of exercise were seen in terms of improved pain intensity and quality of life. Altogether, exercise may be an effective treatment for FM symptoms. Thus, aerobic exercise and strength training are effective programs for the treatment of FM. By summarizing the findings and effect sizes of the reviewed studies, we observed that the evidence for improvement of pain level and quality of life was the strongest. The results have potential to influence evidence-based practice. Future studies should analyze the long-term effects of exercise.